The cost-effectiveness of integrating simplified HCV testing into HIV pre-exposure prophylaxis (PrEP) and treatment services among men who have sex with men in TaiwanResearch in context - Huei-Jiuan Wu; Tanya L. Applegate; Jisoo A. Kwon; Evan B. Cunningham; Jason Grebely; Richard T. Gray; Sophy T.F. Shih (Elsevier, 2024)
Summary: Background: Simplified hepatitis C virus (HCV) testing integrated into existing HIV services has the potential to improve HCV diagnoses and treatment. We evaluated the cost-effectiveness of integrating different simplified HCV testing strategies into existing HIV pre-exposure prophylaxis (PrEP) and treatment services among men who have sex with men (MSM) in Taiwan. Methods: Mathematical modeling was used to assess the cost-effectiveness of integrating simplified HCV tests (point-of-care antibody, reflex RNA, or immediate point-of-care RNA) with HCV treatment into existing HIV prevention and care for MSM from a healthcare perspective. The impact of increasing PrEP and HIV treatment coverage among MSM in combination with these HCV testing strategies was also considered. We reported lifetime costs (2022 US dollars) and quality-adjusted life years (QALYs) and calculated incremental cost-effectiveness ratios (ICERs) with a 3% annual discounting rate. Findings: Point-of-care HCV antibody and reflex RNA testing are cost-effective compared to current HCV testing in all PrEP and HIV treatment coverage scenarios (ICERs <$32,811/QALY gained). Immediate point-of-care RNA testing would be only cost-effective compared to the current HCV testing if coverage of HIV services remained unchanged. Point-of-care antibody testing in an unchanged HIV services coverage scenario and all simplified HCV testing strategies in scenarios that increased both HIV PrEP and treatment coverage form an efficient frontier, indicating best value for money strategies. Interpretation: Our findings support the integration of simplified HCV testing and people-centered services for MSM and highlight the economic benefits of integrating simplified HCV testing into existing services for MSM alongside HIV PrEP and treatment. Funding: This study was made possible as part of a research-funded PhD being undertaken by HJW under the UNSW Sydney Scientia scholarship and was associated with the Rapid Point of Care Research Consortium for infectious disease in the Asia Pacific (RAPID), which is funded by an NHMRC Centre for Research Excellence. JG is supported by a National Health and Medical Research Council Investigator Grant (1176131).